ANALISIS KINERJA PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) 2 MWp SUMALATA BERDASARKAN PERFORMANCE RATIO (PR) - Julpandi gobel; Romi Djafar; Ervan Hasan Harun; Jamal Darusalam Giu (Journal Of Renewable Energy Engineering, 2026)
The performance of Solar Power Plants (PLTS) in tropical regions is significantly influenced by fluctuations in environmental parameters and system operational effectiveness. This study evaluates the performance of a 2 MWp grid-connected solar PV plant in Sumalata, Gorontalo, utilizing the Performance Ratio (PR) as the primary metric during the seasonal transition period (October–December 2025). Data were harvested from a SCADA monitoring system to analyze the correlation among energy yield, solar irradiation, and performance degradation. The results demonstrate monthly PR values of 75% (October), 74.2% (November), and 64.2% (December), with a mean period efficiency of 71.1%. The significant decline in PR during December is attributed to environmental factors, specifically increased cloud cover and humidity, as well as technical constraints such as module soiling accumulation and inverter operational disturbances. These findings underscore that, while the average performance remains within the operational benchmark (70%), adaptive Operation and Maintenance (O&M) strategies tailored to the humid tropical climate are essential to ensure long-term stability in system efficiency.